Raspberry pi system software reference - Gay, Warren W. (Apress, 2014)
Raspberry Pi is Linux, but it's a unique flavor of Linux, specifically for the ARM-based Pi. Raspberry Pi Software Reference guides you through the boot process, including options for tweaking HDMI, memory, and other boot options. You'll learn the details of run levels and creating new services, and how to use the custom command vcgencmd for doing things like reporting temperature, clock speeds, and voltage. And while there are cross-compilers available for some flavors of Linux, one of the most important things you'll get from Raspberry Pi Software Reference is how to build your own Raspberry Pi cross-compiler on your Mac OSX, Linux, or Windows computer.